Pengaruh Anggaran Kas sebagai Alat Perencanaan dan Pengendalian Terhadap Tingkat Likuiditas Pada Toko Kue Dapur Amien - Vince Ariany; Sinta Sintia (Juripol (Jurnal Institusi Politeknik Ganesha Medan), 2020)
The purpose of this study was to determine the effect of the cash budget, as a planning and control tool on the level of liquidity in the Amien Kitchen Cake Shop. This research uses descriptive qualitative method. Analysis is done by collecting data and analyzing how to use the cash budget to make comparisons between theory and practice and set forth to explain an explanation of the numbers and then explained again in the form of prose or standard language description. The results of this study accept that the cash budget as a planning tool and cash budget as a control tool together have a significant influence on the level of liquidity.